Index to trade information sources on the internet (ITC GenevaCH, 1999)
Provides internet addresses for sites that deal with the following:- company registers; exchange rates; norms and standards; press agency news; price information; statistics; tariffs and other trade control measures; trade barriers; trade regulations; tenders; government procurement; trade events; exhibitions; trade and business opportunities.
DC